Szabó Árpád klasszikus filológus, tudománytörténész életrajzi kronológiája Születése 100. évfordulójának tiszteletére - Gazda, István (Gerundium, 2015)
THE BIOGRAPHY OF ÁRPÁD SZABÓ CLASSICAL PHILOLOGIST AND HISTORIAN OF SCIENCE. his collection of data reviews the most signiicant events of the long career of Árpád Szabó (1913–2000), an internationally recognized classical philologist and historian of science. He worked as a university teacher at the University of Debrecen, later moved to Budapest, but due o his role in the 1956 hapennings, he did not get a chance of teaching in Hungary until the 1990s. From the end of the 1950s he was an associate at the Institute of Mathematics of the Hungarian Academy of Science, and during this period, against his political background, he had a compelling scientiic career. he chronology reviews his most important works, his lectures abroad and his role in the international scientiic circles.